Surgical menopause – benefits early initiation estrogen replacement therapy - Paszkowski, Tomasz; Woźniakowska, Ewa (Menopause Review/Przegląd Menopauzalny, 2004)
Bilateral salpingoophorectomy results in dramatic decreases in estrogen, progesterone and testosterone blood levels. Surgical menopause in premenopausal women causes important somatic and physiologic changes such as menopause symptoms which can have profound negative effects on normal activities of daily living and quality of life and long-term chronic disease, particulary cardiovascular disease and osteoporosis. Observational epidemiological studies suggest that a major step after surgical intervention is initiation of estrogen replacement therapy as soon as possibile. Early initiation of estrogen replacement therapy is recomended to prevent the complications. This article presents several beneficial health effects estrogen replacement therapy.